2012
DOI: 10.1111/j.1530-9290.2012.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Carbon and Temporary Storage Addressed with Dynamic Life Cycle Assessment

Abstract: Key words:carbon footprint carbon storage climate change global warming industrial ecology time Summary A growing tendency in policy making and carbon footprint estimation gives value to temporary carbon storage in biomass products or to delayed greenhouse gas (GHG) emissions. Some life cycle-based methods, such as the British publicly available specification (PAS) 2050 or the recently published European Commission's International Reference Life Cycle Data System (ILCD) Handbook, address this issue. This artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(188 citation statements)
references
References 26 publications
5
157
0
2
Order By: Relevance
“…This is consistent with the results obtained by Fouquet et al [14] and Levasseur et al. [15], where it was also found that timing of the forest growth significantly affects the outcome of this kind of study. Similarly, in the study by Fouquet et al [15] where single-family houses were analyzed, the difference between a concrete house and a timber alternative varies when a dynamic approach is applied to calculate climate impacts, even though the ranking between them stays the same, which is also consistent with the results obtained in this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is consistent with the results obtained by Fouquet et al [14] and Levasseur et al. [15], where it was also found that timing of the forest growth significantly affects the outcome of this kind of study. Similarly, in the study by Fouquet et al [15] where single-family houses were analyzed, the difference between a concrete house and a timber alternative varies when a dynamic approach is applied to calculate climate impacts, even though the ranking between them stays the same, which is also consistent with the results obtained in this study.…”
Section: Discussionsupporting
confidence: 83%
“…[15], where it was also found that timing of the forest growth significantly affects the outcome of this kind of study. Similarly, in the study by Fouquet et al [15] where single-family houses were analyzed, the difference between a concrete house and a timber alternative varies when a dynamic approach is applied to calculate climate impacts, even though the ranking between them stays the same, which is also consistent with the results obtained in this study. This study and the study by Fouquet et al [14] differ not only in the type of building analyzed but also in the assumptions explored besides the time horizon and timing of the forest carbon sequestration.…”
Section: Discussionmentioning
confidence: 99%
“…There are however, some differences if only the carbon contained in the harvested stem is included or if other pools like below-ground carbon are included. Levasseur et al (2013) requires the inventory result (sum of the positive and negative emissions) of the given GHG for each year (in kg) for the time horizon.…”
Section: Data Needs For Emerging Methods For Biogenic Carbonmentioning
confidence: 99%
“…The methodology developed in Levasseur et al (2010) and applied in Levasseur et al (2013), proposes the inclusion of time series in the LCA calculations. This is defined by the authors as a dynamic LCA.…”
Section: Dynamic Life Cycle Assessmentmentioning
confidence: 99%
“…As a result, the biogenic carbon balance was agreed to be consequently omitted. However, this widely used assumption about carbon neutrality is criticized because it ignored a significant time lag between biogenic carbon absorption and emissions that is caused by temporary carbon storage [4,15,18,[39][40][41]. Regarding time change, wood continues to store carbon for a certain period, and the timing of wood incineration or biodegradation and growth in forests varies.…”
Section: Introductionmentioning
confidence: 99%